First evidence of white sharks, Carcharodon carcharias, in the tongue of the ocean, central Bahamas - Guttridge, T. L.; Matich, P.; Guttridge, A. E.; Winton, M.; Dedman, S.; Skomal, G. (Frontiers in Marine Science, 2024)
The white shark, Carcharodon carcharias, is an iconic apex predator, playing an important ecological role across its range. Persistent bycatch and overfishing led to white shark declines, but recent studies in the North Western Atlantic (NWA) revealed evidence for regional recovery, and highlighted the importance of Southeastern Florida and the Gulf of Mexico as overwintering grounds for maturing white sharks. However, despite its proximity to Florida and comparably productive habitats, records of white sharks in The Bahamas are extremely rare, with a comprehensive survey of sightings and captures describing only one white shark between 1800 - 2010. Here, we reveal acoustic tracking detections of ten white sharks from 2020 - 2024 along the western edge of the Tongue of the Ocean off Central Andros Island, The Bahamas. White sharks were originally tagged off the coast of the United States and Canada, and detected off Andros Island, The Bahamas from November-May. White sharks were detected along the drop-off zone of the reef at ca. 25 m, exclusively between dusk and dawn, with the number of detections suggesting transient behavior. These findings expand our knowledge of white shark distribution in the NWA, highlighting data gaps in The Bahamas and underlining the importance of collaborative protective measures for species recovery.